Penerapan Pembelajaran Materi Teks Laporan Hasil Observasi Kelas VII Berdasarkan Kurikulum 2013 (Studi Kasus: SMP PGRI 4 Bagorejo) - Alfi Khoiru An Nisa; Rahayu Pristiwati; Mukh Doyin (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the suitability of the lesson plans for the text of the observation report at SMP PGRI 4 Bagorejo with the K-13 standard, describe the suitability of the lesson plans that have been made with the learning process, and also describe the suitability of the assessment sheet with the K-13 standard. This research belongs to the type of qualitative research with a descriptive approach, the data source used is the Indonesian language teacher at SMP PGRI 4 Bagorejo. Data collection techniques through observation, documentation and interviews, and data analysis was carried out with reference to the K-13 standard. The results of the study show (1) that the lesson plans for the text material from the observations of class VII made by the Indonesian language teacher at SMP PGRI Bagorejo are in accordance with the 2013 curriculum process standards, (2) the implementation of learning the text material from the observations of class VII is in accordance with the lesson plans that refer to the standard the K-13 process, and (3) the assessment sheet that has been made by the teacher in accordance with the K-13 standard contains an assessment of 3 domains, namely cognitive, psychomotor, and attitude.